Service level agreement and provisioning in optical networks. - Fawaz, W.
This article proposes a service level agreement applied to the optical domain (O-SLA), which is expected to be the near- and long-term network technology of the great bandwidth capacity offered by optical devices. After an exposition of the rationale behind an optical SLA, parameters that could be included in this O-SLA, as well as their values for four classes of services are proposed. Different client (wavelength or subwavelength) and service types (from leased wavelength to bandwidth on demand) are distinguished when necessary. The last part of this article presents issues related to the provisioning of services emanating from this O-SLA.
Keywords: GMPLS; SLA; Bandwidth capacity; Generalized multiprotocol label switching management; Optical networks; Optical service level agreement; Provisioning process; Service types; Traffic; Wavelength